THE EFFECT OF TQM PRACTICES ON KNOWLEDGE SHARING : CASE OF MOROCCAN AGRIBUSINESS COMPANIES - BICHANI, Hafsa; BOUBRAHIMI, Nabil (Revue du contrôle, de la comptabilité et de l’audit, 2020)
This paper addresses the issue of TQM practices in agribusiness firms to demonstrate that they have a critical effect on knowledge sharing. The discourse on the importance of knowledge sharing has invaded firms and has become a major necessity. This paper aims to highlight the role of total quality management practices, after the wave of information, to make visible the knowledge and know-how of the organization as a factor for improving the problem. knowledge management. Semi-structured interviews were conducted as part of this study. The research sample consisted of 8 companies with employees from the middle and top level of management. Evidence shows that, first, all respondents recognized the importance and need for knowledge sharing. Second, it shows that for successful knowledge sharing, TQM practices need to be constantly improved.